A POSSIBLE CRITIQUE ON BAHTIN’S INTERPRETATION OF DOSTOEVSKY - Stojanov, Trajce (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
This paper is an effort for some different approach of Dostoevsky`s poetic concerning Bahtin`s interpretation. Namely, the paper is a critical overview of Bahtin`s interpretation on Dostoevsky`s “polyphonic novel” offering completely different interpretation of Dostoevsky`s work. Bahtin`s interpretation of Dostoevsky is quite revolutionary and logically consistent, but in our opinion, it misses out the crucial nature of Dostoevsky`s work. Our approach enables us to overcome the obstacles because of which Bahtin made that interpretation in the first place. Bahtin considered that “philosophical monologization” in interpretation of Dostoevsky`s poetic is inappropriate and that`s why he offered his structural analysis and the concept of “polyphonic novel”. But that kind of approach tears living unity of Dostoevsky’s novel – in best case, or lacks of understanding of Dostoevsky`s philosophy – in worst case. Our approach seeks solution in synthesis which is actually immanent in Dostoevsky`s dialectic.